Towards Developing a Courseware for Physical Education : Methods and Implementation - Noorasikin, Ismail (2004)
This project focuses on the methods and development of a multimedia courseware called the Interactive-Learning for Physical Education (InteL-PE). This courseware was produced according to the Pragmatic Model developed by Carswell and Murphy (1995). This particular model was chosen due to its apparently straightforward steps. This courseware, which concentrates on a topic taken from the Malaysian Form Five Physical and Health Education (Pendidikan Jasmani dan Kesihatan or PJK) syllabus, uses the combination of texts, video, audio, and animation; produced as teaching aids for teachers and learning aids for students. It focuses on PJK because of the apparent lack of acceptance and credibility of the subject in Malaysian education scenario despite being a core subject. A series of evaluation have been conducted for InteL-PE and the findings showed that the courseware can be used to motivate students, and as a new teaching methodology that can provide teaching aid variety to teachers especially non-option teachers teaching PJK in Malaysian schools.